Multi-Criteria Decision Making in the Milling Process Using the PARIS Method - Le, H. K. (Engineering, Technology & Applied Science Research, 2022)
The Multi-Criteria Decision-Making (MCDM) process of milling SNCM439 steel is presented in this study. In this experimental study, 3 cutting tool parameters, namely the number of pieces, cutting piece material, and tip radius were considered and 3 cutting mode parameters, i.e. cutting speed, feed rate, and depth of cut changed in each experiment. SR and MRR are selected as the output parameters of the milling process. The PARIS method was used for MCDM, in which, the weights of SR and MRR were determined by 3 methods, namely AW, EW, and MW. Twenty-seven sets of ranking results for 27 alternatives (experiments) are presented. The GINI index was used to evaluate the stability of ranking alternatives. The results have determined the value of 6 input parameters to ensure the minimum SR and the maximum MRR simultaneously.